2019
DOI: 10.1021/acsaelm.9b00623
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Persistent Photoconductivity Effect in Zinc Oxide by Sequential Surface Ultraviolet Ozone and Annealing Treatments

Abstract: We developed a method to reduce the persistent photoconductivity (PPC) effect of zinc oxide (ZnO) thin film transistors (TFTs) by sequential surface treatment, which includes preannealing/ultraviolet ozone/postannealing (PUP) treatments. Preannealing treatment improves the surface uniformity of the film and eliminates the residual solvent and contaminant molecules without affecting the zinc–oxygen bonds. The ultraviolet ozone (UVO) treatment reduces the oxygen vacancy and increases the amount of metal hydroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
(121 reference statements)
0
24
0
Order By: Relevance
“…demonstrated a method to reduce the PPC issue by sequential surface treatment, which includes pre‐annealing, UV–ozone treatment, and post‐annealing treatment as shown in Figure a. [ 72 ] In each step, the ZnO film was affected in three effects by the treatment: 1) pre‐annealing treatment improved the surface uniformity of the ZnO film and reduced the residual solvent, 2) UV–ozone treatment decreased the oxygen vacancy, and 3) post‐annealing treatment refined the ZnO film density and induced zinc–oxygen bonding. Owing to the improved film quality, the photoelectric recovery time after the irradiation of the UV light was shortened, indicating that the PPC effect on the ZnO phototransistor is decreased as shown in Figure 7b.…”
Section: Classification Of Metal Oxide Phototransistors By Absorption Layermentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated a method to reduce the PPC issue by sequential surface treatment, which includes pre‐annealing, UV–ozone treatment, and post‐annealing treatment as shown in Figure a. [ 72 ] In each step, the ZnO film was affected in three effects by the treatment: 1) pre‐annealing treatment improved the surface uniformity of the ZnO film and reduced the residual solvent, 2) UV–ozone treatment decreased the oxygen vacancy, and 3) post‐annealing treatment refined the ZnO film density and induced zinc–oxygen bonding. Owing to the improved film quality, the photoelectric recovery time after the irradiation of the UV light was shortened, indicating that the PPC effect on the ZnO phototransistor is decreased as shown in Figure 7b.…”
Section: Classification Of Metal Oxide Phototransistors By Absorption Layermentioning
confidence: 99%
“…The inset shows the graph on a log scale for the initial 4 s. a,b) Reproduced with permission. [ 72 ] Copyright 2019, American Chemical Society. c) Schematic diagram of IGZO film with hydrogen rich Al 2 O 3 dielectric structure.…”
Section: Classification Of Metal Oxide Phototransistors By Absorption Layermentioning
confidence: 99%
“…We compared the optoelectronic characteristics of previous research related to oxide phototransistors without an absorption layer to confirm the performance of our devices, as shown in Table S1 (Supporting Information). [ 39–52 ] PDMS treatment significantly enhanced the detection ability of IGZO phototransistors in the visible region.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been proposed to overcome this issue from a material, structural, and circuit point of view. Many studies have aimed to reduce the oxygen vacancies in the semiconductor by annealing in oxidizing conditions such as high-pressure oxygen or ultraviolet ozone gas, doping of similar size anion elements such as nitrogen and sulfur, and controlling the metal–cation ratio of the multicomponent oxide semiconductor . Several studies have reported a reduction of the PPC while reacting with the visible or near-infrared light of organic/inorganic or low-dimensional material/inorganic hybrid structure devices. , With regard to material or structural approaches, some studies considered the applied gate bias pulse sequence, which can rapidly recombine generated electron–hole pairs or trapped carriers upon light exposure. , However, these methods come with their own challenges, including difficulty controlling the process conditions, the unintended interface with the ex situ process, and the need for an additional circuit and metal line for the gate pulse bias.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been proposed to overcome this issue from a material, structural, and circuit point of view. Many studies have aimed to reduce the oxygen vacancies in the semiconductor by annealing in oxidizing conditions such as high-pressure oxygen 7 or ultraviolet ozone gas, 8 doping of similar size anion elements such as nitrogen and sulfur, 9 and controlling the metal−cation ratio of the multicomponent oxide semiconductor. 10 Several studies have reported a reduction of the PPC while reacting with the visible or nearinfrared light of organic/inorganic or low-dimensional material/inorganic hybrid structure devices.…”
Section: ■ Introductionmentioning
confidence: 99%